Robotic Colorectal Surgery using Senhance® Robotic Platform: Single Center Experience with First 13 Cases - Samalavičius, Narimantas Evaldas; Deduchovas, Olegas (Lietuvos chirurgija, 2019)
[full article, abstract in English; abstract in Lithuanian] Until recently, robotic surgery has been associated only with da Vinci robotic system. A novel Senhance® robotic system (TransEnterix Surgical Inc., Morrisville, NC, USA) has been introduced almost 5 years ago. Published reports on experience in colorectal surgery using this robotic platform is very limited. We present a prospective analysis of first 13 robotic colorectal surgeries in Klaipėda University Hospital, Klaipėda, Lithuania. 13 patients underwent various colorectal resections: 10 for colorectal cancer and 3 for colonic polyps. 7 were men and 6 women, age range 32–77 years, on an average 56 years. Among 10 patients with colorectal cancer, 3 had stage I, 3 stage II, 3 stage III and 1 stage IV colorectal cancer. 2 patients were operated for unremovable ascending colon adenomas and 1 underwent prophylactic subtotal colectomy with ileorectal anastomisis for familial adenomatous polyposis. Complication occurred in 1 case (7.7%). This patient underwent robotic abdominoperineal resection for low rectal cancer, developed postoperative bleeding from perineal wound on day 7 and had to be taken to operative room for oversuturing the bleeding vessel. Operative time was on an average 3 hours 50 minutes, ranging from 2 hours and 55 minutes to 6 hours and 10 minutes. In-hospital stay ranged from 5 to 16 days, on an average 7 days. Conclusion. Our experience with different types of robotic colorectal resections allows us to state that Senhance® robotic system is feasible and safe for colorectal surgery, and wider implementation of this system in our specialty worldwide is simply a question of time.